Perceptual-cognitive expertise in elite volleyball players - Alves, H.; Voss, M. W.; Boot, W. R.; Deslandes, A.; Cossich, V.; Inacio Salles, J.; Kramer, A. F. (Frontiers in Psychology, 2013)
The goal of the current study was to investigate the relationship between sport expertise and perceptual and cognitive skills, as measured by the component skills approach. We hypothesized that athletes would outperform non-athlete controls in a number of perceptual and cognitive domains and that sport expertise would minimize gender differences. A total of 154 individuals (87 professional volleyball players and 67 non-athlete controls) participated in the study. Participants performed a cognitive battery, which included tests of executive control, memory, and visuo-spatial attention. Athletes showed superior performance speed on three tasks (two executive control tasks and one visuo-spatial attentional processing task). In a subset of tasks, gender effects were observed mainly in the control group, supporting the notion that athletic experience can reduce traditional gender effects. The expertise effects obtained substantiate the view that laboratory tests of cognition may indeed enlighten the sport-cognition relationship.